Nursing students’ experiences with the integration of flexible learning in the clinical skills centre - Ahmad, Norfadzilah; Lee, Siew Pien; Abd Aziz, Zuraidah; Ismail, Zarina (Malaysian Nurses Association, 2023)
Background: In nursing education, flexible learning is highly regarded since it offers students a variety of readily accessible, customized learning opportunities. By successfully developing clinical competency outside of the conventional paradigm, this model guarantees that nursing students will have the abilities necessary to adapt to the constantly changing healthcare environment.